2006
DOI: 10.1614/ws-05-051r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humectants on the uptake and efficacy of glufosinate in wild oat (Avena fatua) plants and isolated cuticles under dry conditions

Abstract: A series of dose–response experiments were performed at low humidity to determine if glufosinate efficacy could be increased by lengthening the drying time through the addition of humectants. Of several humectants evaluated, only 5% glycerol or 5% triethylene glycol when applied with glufosinate produced dry weight reductions and mortality similar to exposure to high humidity.14C-glufosinate movement through isolated wild oat cuticles was greater at high humidity, poorest at low humidity, but intermediate at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
0
19
1
3
Order By: Relevance
“…In contrast to temperature, relative humidity did not influence weed response to herbicide stress. Similar results were reported by F a u s e y and R e n n e r [17], but generally this finding is inconsistent with most of the previous papers that have proven a weaker response of weeds to herbicides at low relative humidity [4,18,19]. The lack of differences in weed response proved in this research may be due to the small differences between the relative humidity levels tested.…”
Section: Discussioncontrasting
confidence: 62%
“…In contrast to temperature, relative humidity did not influence weed response to herbicide stress. Similar results were reported by F a u s e y and R e n n e r [17], but generally this finding is inconsistent with most of the previous papers that have proven a weaker response of weeds to herbicides at low relative humidity [4,18,19]. The lack of differences in weed response proved in this research may be due to the small differences between the relative humidity levels tested.…”
Section: Discussioncontrasting
confidence: 62%
“…After evaporation, crystals containing the active ingredient can be formed, preventing its absorption (Yu et al 2009b, Xu et al 2011. By increasing the evaporation time, the pesticide efficacy can be improved (Ramsey et al 2006). Nevertheless, the product runoff needs to be evaluated (Yu et al 2009a), mainly when higher carrier volumes are used.…”
Section: Resultsmentioning
confidence: 99%
“…In the majority of cases, applications should be avoided when the relative air humidity is lower than 50 % and temperature is higher than 30 ºC. Ramsey et al (2006) observed that the relative air humidity has a great effect on foliar pesticide applications, mainly on the cuticle of the plant and also on the evaporation and deposition of droplets. Zhu et al (2008) evaluated the evaporation time of droplets deposited on non-lipophilic surfaces under different relative air humidity conditions, evidencing that a reduction of 30 % in relative air humidity caused an average reduction of 34 % in the evaporation time of droplets.…”
Section: Key-wordsmentioning
confidence: 99%
“…De acordo com Ramsey et al (2006) a umidade do ar tem grande efeito na aplicação de agrotóxicos foliares, principalmente sobre a cutícula da planta e também sobre a evaporação e deposição das gotas. Além das condições ambientais, o uso de adjuvantes também pode influenciar a evaporação de gotas depositadas.…”
Section: Introductionunclassified